'Communism … is the affirmation of a new community': Notes on Jacques Camatte. (June 2014) - el-Ojeili, Chamsy
This article explores the work of the primitivist communist Jacques Camatte. Camatte emerges from the Bordigist current of Marxism, and the article begins with an examination of the major emphases in Amadeo Bordiga's thought: the central role of the party as 'social brain'; the critique of democracy and electoral activity; the rejection of individualism, and the insistence on the social, community-centred character of communism. This background is crucial to Camatte's early work, but also to his later break from Bordigism and Marxism. This break occurred at the end of the 1960s, and the second part of the article follows Camatte's primitivist writings. Here, Camatte continues to think of communism as community/Gemeinwesen, but fundamentally re-orients his thinking on class, organisation, and communist transformation, in light of an extension of his initial focus on capital's 'running away', its establishment as material community. The concluding note critically draws together Camatte's thinking and later English-language primitivist work, suggesting that despite major problems, his work remains of interest.